Comorbidities and Presenting Symptoms in a Real-World Population With Obstructive Sleep Apnea. (April 2023) - Parthasarathy, Sairam; Zhang, Jerry; Hyman, Danielle; Doherty, James; Saad, Ragy; Fox, Benjamin; Marshall, Nell J.; Parks, Gregory
Abstract: Background: Obstructive sleep apnea (OSA) is a highly prevalent sleep disorder that is often associated with numerous medical and psychiatric comorbidities. Patients with OSA experience a variety of symptoms that can be burdensome and affect their quality of life and satisfaction with care. Excessive daytime sleepiness (EDS) is a common symptom of OSA, and can persist despite primary airway therapy (e.g., positive airway pressure [PAP]). This analysis aimed to characterize common comorbidities, as well as symptoms present at OSA diagnosis and their burden in a real-world population of participants with OSA. Methods: US residents (≥18 years of age, self-reported clinician diagnosis of OSA [from 1/1/2015 to 3/31/2020]) completed a survey in Evidation Health's Achievement app that assessed self-reported sleepiness (Epworth Sleepiness Scale [ESS]), self-reported PAP usage, self-reported physician-diagnosed comorbidities, and information on their symptoms at time of OSA diagnosis. Self-reported PAP use was categorized as nonuse (no PAP use), nonadherent (<4 h/night or <5 d/wk), intermediate (4–6 h/night, ≥5 d/wk), or highly adherent (≥6 h/night, ≥5 d/wk). EDS was defined as ESS score >10. All data were summarized descriptively. Results: In total, 2289 participants completed the survey (50.3% female; 82.5% White; mean ± standard deviation [SD] age, 44.8 ± 11.1 years; mean ± SD age at OSA diagnosis, 40.7 ± 11.4 years; mean ± SD body mass index, 35.4 ± 8.7 kg/m 2 ); 42.5% had EDS. Among the total population, 30.6% were PAP non-users, 6.7% were nonadherent, 9.8% were intermediate adherent, and 52.9% were highly adherent. Across the study population, the most common self-reported physician-diagnosed comorbidities were anxiety (44%) and depression (42%) followed by hypertension (39%), dyslipidemia (26%), and asthma (21%). Among the symptoms participants reported having had at the time of OSA diagnosis, the most common were EDS (79%), fatigue (79%), snoring (75%), and awakening with a dry mouth or sore throat (63%). Concentration/Memory problems (48%) and mood changes (46%) were also common. In the overall population, the symptoms present at the time of OSA diagnosis that were most likely to be highly burdensome were fatigue (53%), EDS (46%), snoring (35%), difficulty concentrating/memory issues (31%), and mood changes (25%). Conclusions: These real-world survey data identify anxiety and depression as the most frequently reported comorbidities in a population of participants with OSA, each affecting over 40% of participants. In addition to classic OSA symptoms (e.g., EDS, fatigue, snoring, and awakening with dry mouth/sore throat), concentration/memory problems and mood changes were also common at the time of OSA diagnosis and were among the presenting symptoms most frequently reported as highly burdensome, along with fatigue, EDS, and snoring. Funding: Axsome Therapeutics and Jazz Pharmaceuticals